Resistance training for rehabilitation after burn injury: A systematic literature review & meta-analysis. Issue 4 (June 2018) - Gittings, Paul M.; Grisbrook, Tiffany L.; Edgar, Dale W.; Wood, Fiona M.; Wand, Benedict M.; O'Connell, Neil E.
Abstract: Background/aim: Resistance training is beneficial for rehabilitation in many clinical conditions, though this has not been systematically reviewed in burns. The objective was to determine the effectiveness of resistance training on muscle strength, lean mass, function, quality of life and pain, in children and adults after burn injury. Methods: Medline & EMBASE, PubMed, CINAHL and CENTRAL were searched from inception to October 2016. Studies were identified that implemented resistance training in rehabilitation. Data were combined and included in meta-analyses for muscle strength and lean mass. Otherwise, narrative analysis was completed. The quality of evidence for each outcome was summarised and rated using the GRADE framework. Results: Eleven studies matched our inclusion criteria. Primary analysis did not demonstrate significant improvements for increasing muscle strength (SMD 0.74, 95% CI −0.02 to 1.50, p = 0.06). Sensitivity analysis to correct an apparent anomaly in published data suggested a positive effect (SMD 0.37, 95% CI 0.08–0.65, p = 0.01). Psychological quality of life demonstrated benefit from training (MD = 25.3, 95% CI 3.94–49.7). All studies were rated as having high risk of bias. The quality of the evidence was rated as low or very low. Conclusion: Further research with robust methodology is recommended to assess the potential benefit suggested in this review.